2017
DOI: 10.21037/jtd.2017.08.53
|View full text |Cite
|
Sign up to set email alerts
|

Distance-saturation product of the 6-minute walk test predicts mortality of patients with non-cystic fibrosis bronchiectasis

Abstract: Background: Previous surveillance methods to monitor the prognoses of patients with bronchiectasis are too complex for use in daily practice. The 6-minute walk test (6MWT) is a simple exercise test to predict the prognosis of chronic obstructive airway disease and numerous chronic lung diseases, including idiopathic pulmonary fibrosis. No studies have investigated exercise-induced oxygen desaturation (EID) and distancesaturation product (DSP) of 6MWT to predict the prognoses of patients with bronchiectasis. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 26 publications
1
30
0
5
Order By: Relevance
“…In another study conducted on patients (patients without cystic fibrosis), it was found that oxygen saturation decreasrdafter the 6-min walk test (HSIEH, et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…In another study conducted on patients (patients without cystic fibrosis), it was found that oxygen saturation decreasrdafter the 6-min walk test (HSIEH, et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…A small study ( n = 27) found that mean 6‐min walk distance (6MWD) had a stronger correlation with HR‐QoL measures then spirometric indices, whilst a Chinese study described higher mortality in those with a lower 6MWD at baseline . Baseline 6MWD of survivors was 467.9 ± 77.1 m compared to 363.7 ± 126.7 m in those who had died 6 years later . Our literature search revealed no published data on non‐spirometric lung function indices in the paediatric population.…”
Section: Monitoringmentioning
confidence: 77%
“…One study using data from a cohort of 111 adults with bronchiectasis described that pulmonary function indices associated with mortality were higher residual volume (RV)/total lung capacity (TLC) ratio (RR: 1.03, 95% CI: 1.01–1.04), lower TLC (RR: 0.95, 95% CI: 0.93–0.98) and lower transfer coefficient of the lung for carbon monoxide (K CO ) (RR: 0.96, 95% CI: 0.94–0.98) . A small study ( n = 27) found that mean 6‐min walk distance (6MWD) had a stronger correlation with HR‐QoL measures then spirometric indices, whilst a Chinese study described higher mortality in those with a lower 6MWD at baseline . Baseline 6MWD of survivors was 467.9 ± 77.1 m compared to 363.7 ± 126.7 m in those who had died 6 years later .…”
Section: Monitoringmentioning
confidence: 99%
“…The product (DSP) of the distance walked in the 6MWT and minimum oxygen saturation (SatO 2 ) obtained during the test includes both variables. As a result, it has been proposed as a predictor of mortality in respiratory diseases like idiopathic pulmonary fibrosis and non‐cystic fibrosis bronchiectasis . However, few studies have evaluated its prognostic ability in patients with COPD at the outpatient level …”
Section: Introductionmentioning
confidence: 99%
“…As a result, it has been proposed as a predictor of mortality in respiratory diseases like idiopathic pulmonary fibrosis and non-cystic fibrosis bronchiectasis. 12,13 However, few studies have evaluated its prognostic ability in patients with COPD at the outpatient level. 14 The objective of this study was to determine the ability of the DSP (m%) to predict mortality in a cohort of patients with COPD being treated at outpatient pulmonology clinics and to compare it to the BODE index and meters walked in the 6MWT (m6MWT).…”
Section: Introductionmentioning
confidence: 99%